Cryptography and randomization to dispose of data and boost system security. Issue 1 (1st January 2017) - Alkhadhr, Shaikhah B.; Alkandari, Mohammad A.
Abstract: Massive public pressure is arising to achieve data privacy and protection. One way to maintain data privacy is to perform efficient data disposal processes. This minimizes the chances of data leakage over an extended period and through irresponsible actions. That is why adequate data disposal is essential in so many governmental and critical institutions. Simply "deleting" data does not erase it. In fact, it only removes the name that refers to that piece of data, but the data itself remains. In this paper, we utilize an encryption algorithm and then perform a randomization process to dispose of data values in an irreversible approach making it difficult to retrieve the original value of data from the defaced result.